ANALISIS GAYA KEPEMIMPINAN DALAM MENINGKATKAN EFEKTIVITAS KINERJA KARYAWAN PADA PT GRAHA SERIBU SATU JAYA - Mochamad Fatchurrohman; M. Syamsul Ma’arif; Fanny Dwi Puspitasari (Media Mahardhika, 2023)
To maximize business outcomes and ensure customer satisfaction, it is crucial to enhance the performance of the staff. The objective of this study is to ascertain the leadership model employed by PT Graha Seribu Satu Jaya and to evaluate its effectiveness in improving employee output at PT Graha Seribu Satu Jaya. The methodology for data collection, analysis of results, and drawing conclusions is an integral part of the qualitative research approach. Literature review, in-depth observations, and extensive interviews with four employees and production supervisors were used as data sources. The research findings are based on the democratic management approach adopted by PT Graha Seribu Satu Jaya. Production supervisors value each other's potential by engaging in activities expected to enhance employee performance effectiveness, the utilization of training, employee performance effectiveness, employee capabilities, and the extent to which employees rely on others for assistance. Employees do not feel sufficiently motivated, leading to a lack of initiative in their work.